(untitled) (Polish Yearbook of International Law, 2025)
Drawing on the theoretical approach of F.W. Scharpf (2012), as critically contested by M. van den Brink, M. Dawson and J. Zglinski (2023), the article un earths the implications for individual rights at the intersection of health protection and freedom of movement of persons in the European Union’s integrated market during the pandemic. The findings are based on empirical analysis of the CJEU case law and European secondary laws adopted in the context of counteracting the COVID-19 pandemic (2020–2022). The text shows that the Court of Justice of the European Union (CJEU) has adopted a variety of approaches in its standard of review towards national regulatory measures (either strict or deferential review), while many secondary laws were adopted at the EU level to pursue market correction policies (e.g. crisis prepared ness or protection of health data). Thus the research confirms that the current internal market dynamics in the areas of health and movement of persons is indeed too complex to be described solely by the original asymmetry thesis. Yet, it is also argued that less de-regulation at the national level (negative integration) and more re-regulation at the EU level (positive integration) does not necessarily lead to better protection and enforcement of Treaty-based and fundamental rights of individuals in the EU.